(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between static balance and dynamic balance of the results of Mawashi Ushiro Geri’s kick in students who participated in karate extracurricular activities at Pemalang 4 Public Middle School. Kick exercises by students so far are monotonous and have not integrated an important balance component for the success of the technique. This study uses a correlational quantitative approach with a Once-Shot study design and involves all karate students who have practised for at least six months as a sample. The instruments used include a standing stab test for static balance, a Y-Balance test for dynamic balance, as well as assessment of kick techniques by Forki-certified judges. The results of the analysis using the Pearson correlation showed a significant positive relationship between static balance and kick results (r = 0.421; p = 0.021) and between dynamic balance and kick results (r = 0.370; p = 0.044). This finding indicates that the two types of balance play an important role in increasing the effectiveness of Mawashi Ushiro Geri’s kick. Therefore, the development of a structured and varied training model with a focus on physical balance is highly recommended in fostering karate in the school environment